Constructing "Qur'anic Diplomacy" at Khamenei's State Funeral: A Critical Discourse Analysis of Sacred Text, Media Framing, And Geopolitical Signaling - Akmal Fajri (Jurnal Bahasa dan Sastra Pusaka Cendekia, 2026)
This study investigates how the notion of "Qur'anic diplomacy" was discursively constructed around differentiated Qur'anic recitations during the July 2026 state funeral ceremonies for Iran's late Supreme Leader, Ayatollah Ali Khamenei. Rather than presuming that each recitation constituted an officially designed diplomatic message, the article treats the episode as a mediated discourse event in which sacred text, ritual sequencing, journalistic framing, and geopolitical knowledge interacted to produce political meaning. The corpus comprises six media texts published between 3 and 6 July 2026 and eight reported verse-delegation pairings, analyzed through Fairclough's three-dimensional Critical Discourse Analysis and van Dijk's socio-cognitive approach. A source-confidence protocol distinguishes verified event facts, reported textual pairings, media interpretations, and scholarly geopolitical inference. The analysis identifies three dominant semantic frames - resistance and steadfastness, calibrated affiliation, and admonition or distance - but shows that their diplomatic force depends on recontextualization rather than on lexical meaning alone. Cross-source comparison also reveals uneven evidentiary stability, most clearly in competing reports concerning Hezbollah. The article contributes the concepts of mediated symbolic diplomacy and evidentiary layering to research on religion, discourse, and international communication. It concludes that Qur'anic recitation can acquire diplomatic salience through ritual placement and media circulation, while claims of intentional state signaling must remain provisional without official documentation or systematic audiovisual verification.   Penelitian ini mengkaji bagaimana gagasan "diplomasi Al-Qur'an" dibentuk secara diskursif melalui pelaporan tentang bacaan ayat Al-Qur'an yang berbeda bagi sejumlah delegasi dalam rangkaian pemakaman kenegaraan Pemimpin Tertinggi Iran, Ayatollah Ali Khamenei, pada Juli 2026. Alih-alih mengasumsikan bahwa setiap bacaan merupakan pesan diplomatik resmi yang dirancang negara, penelitian memandang peristiwa tersebut sebagai peristiwa wacana termediatisasi yang mempertemukan teks suci, urutan ritual, framing jurnalistik, dan pengetahuan geopolitik. Korpus penelitian terdiri atas enam teks media yang terbit pada 3-6 Juli 2026 dan delapan pasangan ayat-delegasi yang dilaporkan. Analisis menggunakan model tiga dimensi Norman Fairclough dan pendekatan sosial-kognitif Teun A. van Dijk, disertai protokol tingkat kepercayaan sumber yang membedakan fakta peristiwa terverifikasi, pasangan ayat yang dilaporkan, interpretasi media, dan inferensi geopolitik akademik. Temuan menunjukkan tiga bingkai semantik dominan: perlawanan dan keteguhan, afiliasi diplomatik yang terukur, serta teguran atau jarak politik. Namun, daya diplomatik ayat tidak berasal dari makna leksikal semata, melainkan dari proses rekontekstualisasi. Perbandingan lintas sumber juga menunjukkan ketidakstabilan bukti, terutama dalam laporan tentang Hizbullah. Studi ini menawarkan konsep diplomasi simbolik termediatisasi dan pelapisan evidensi sebagai kontribusi metodologis bagi kajian agama, wacana, dan komunikasi internasional. Klaim mengenai intensi politik negara tetap harus bersifat tentatif tanpa dokumentasi resmi atau verifikasi audiovisual yang sistematis.   تبحث هذه الدراسة في الكيفية التي تشكّل بها مفهوم «الدبلوماسية القرآنية» خطابيا حول تالوة آيات مختلفة من القرآن الكريم أثناء مراسم الجنازة الرسمية للمرشد الأعلى الإيراني الراحل آية الله علي خامنئي في يوليو/تموز 2026. ولا تفترض الدراسة مسبقا أن كل تلاوة كانت رسالة دبلوماسية رسمية مقصودة، بل تتعامل مع الحدث بوصفه واقعة خطابية وسيطية تتفاعل فيها قدسية النص، وتسلسل الطقس، والتأطير الإعلامي، والمعرفة الجيوسياسية لإنتاج المعنى السياسي. تتكون المدونة من ستة نصوص إعلامية منشورة بين 3 و6 يوليو/تموز 2026 وثمانية اقترانات مبلّغ عنها بين آيات ووفود. وتعتمد الدراسة نموذج نورمان فيركلاف ثلاثي الأبعاد في تحليل الخطاب النقدي والمنظور الاجتماعي المعرفي لتيو فان دايك، مع بروتوكول لتقدير موثوقية الأدلة يميز بين وقائع الحدث المتحققة، والاقترانات النصية المبلّغ عنها، والتفسيرات الإعلامية، والاستدلالات الجيوسياسية الأكاديمية. تكشف النتائج ثلاثة أطر دلالية رئيسة: المقاومة والثبات، والتقارب الدبلوماسي المحسوب، والعتاب أو المسافة السياسية. وتبين الدراسة أن الدلالة الدبلوماسية لا تنبع من المعنى المعجمي للآيات وحده، بل من إعادة سياقها داخل الطقس والتغطية الإعلامية. كما تكشف المقارنة بين المصادر تفاوتا في ثبات الأدلة، ولا سيما في التقارير المتعلقة بحزب الله. وتقترح الدراسة مفهومي «الدبلوماسية الرمزية الوسيطية» و«طبقات الأدلة» إسهاما في دراسة الدين والخطاب والاتصال الدولي، مع التأكيد أن نسبة القصد السياسي المباشر إلى الدولة تظل مؤقتة ما لم تدعمها وثائق رسمية أو أدلة سمعية بصرية منهجية.